Mulberry based zinc nano-particles mitigate salinity induced toxic effects and improve the grain yield and zinc bio-fortification of wheat by improving antioxidant activities, photosynthetic performance, and accumulation of osmolytes and hormones - Chattha, Muhammad Umer; Amjad, Tahira; Khan, Imran; Nawaz, Muhammad; Ali, Muqarrab; Chattha, Muhammad Bilal; Ali, Hayssam M.; Ghareeb, Rehab Y.; Abdelsalam, Nader R.; Azmat, Saira; Barbanti, Lorenzo; Hassan, Muhammad Umair (Frontiers in Plant Science, 2022)
Salinity stress (SS) is a most challenging abiotic stress that limits crop growth and productivity. Therefore, sustainable and cost effective methods are needed to improve crop production and decrease the deleterious impacts of SS. Zinc (Zn) nano-particles (NPs) have emerged as an important approach to regulate plant tolerance against SS. However, mechanisms of SS tolerance mediated by Zn-NPs are not fully explained. Thus, this study was performed to explore the role of Zn-NPs (seed priming and foliar spray) in reducing the deleterious impacts of SS on wheat plants. The study comprised different SS levels: control, 6 and 12 dS m-1, and different treatments of Zn-NPs: control, seed priming (40 ppm), foliar spray (20 ppm) and their combination. Salinity stress markedly reduced the plant growth, biomass and grain yield; all this was associated with enhanced electrolyte leakage (EL), malondialdehyde (MDA), hydrogen peroxide (H2O2), sodium (Na), chloride (Cl) accumulation, and reduced photosynthetic pigments, relative water contents (RWC), photosynthetic rate (Pn), transpiration rate (Tr), stomata conductance (Gs), water use efficiency (WUE), free amino acids (FAA), total soluble protein (TSP), indole acetic acid (IAA), gibberellic acid (GA) and nutrients (Ca, Mg, K, N and P). However, the application of Zn-NPs significantly improved the yield of the wheat crop, which was associated with reduced abscisic acid (ABA), MDA, H2O2 concentration and EL, owing to improved antioxidant activities, and an increase in RWC, Pn, Tr, WUE, and accumulation of osmoregulating compounds (proline, soluble sugars, TSP, FAA) and hormones (GA and IAA). Further, Zn-NPs contrasted the salinity induced uptake of toxic ions (Na and Cl) and increased the uptake of Ca, K, Mg, N and P. Additionally, Zn-NPs application substantially increased the grain Zn bio-fortification of the wheat crop. Therefore, these findings suggest that the exogenous application of Zn-NPs can improve the growth, yield and grain Zn bio-fortification of wheat, while at the same time mitigating the adverse effects of SS through improved physiological functioning, enhanced antioxidant activities, sustained hormones and osmolytes accumulation.